Revelations of humanity : anthropological dimensions of theological controversies - Schenk, Richard (Thomistic ressourcement series, 2022)
"Revelations of Humanity brings together essays into the history and actuality of how our searches for God and for our own humanity are interwoven. They argue that the revelation of God is possible only when accompanied by a revelation of what it means to be a human being. Many of the essays involve a recollection of the thought of Thomas Aquinas. The book is divided into three sections. The first asks about the reality and limits of the human capacity for truth. The second cluster is structured around the four involvements that the Second Vatican Council identified as the human face of genuine Christian existence: participation in the legitimate joys, hopes, sorrows and fears of the contemporary world. The final cluster brings together anthropological dimensions of current ecumenical and interreligious disputes"--